Effectiveness of Classic Versions of Options Pricing Models in Recent Waves of Financial Upheavals - Vipul Kumar Singh,; Naseem Ahmad, (Asian Academy of Management Journal of Accounting and Finance, 2013)
This paper attempts to determine the best alternative model of options pricing with the capacity to control both the level of skewness and kurtosis. It aims to replicate the effectiveness of classic stochastic and deterministic option pricing models and also establish a correlation between the underlying stock returns and their volatility. The paper follows a structural approach for analysing the Hull-White model (with two stochastic versions: non-related and correlated) with respect to the Black-Scholes model, which is a benchmark model. The focus is on fabricating such a model for predicting and protecting the market options price during uncertain financial upheavals. The suggested models have been tested in extreme conditions to determine effectiveness. Furthermore, the paper also examines the hedging effectiveness of hypothecated models.